Elite speed sprint and all-round skaters: functionality rating componential analysis - Titlov, A. Yu.; Shirkovets, E. A. (Theory and Practice of Physical Culture, 2019)
The article analyzes the skaters` working capacity rates obtained in standard laboratory conditions. The physical fitness of the athletes was rated by stepped tests till refusal, with the test time determined by the actual functionality rates of the athletes. The tests included analyses of the exhale and blood lactate at every stage of the tests to estimate the maximal power and aerobic/ anaerobic thresholds. The speed-strength qualities were rated by a strain gauge platform, with the maximal leg extension strength and one/ two leg jump time fixed in the tests. Sampled for the study were 24 elite skaters qualified MS to WCMS and having the close track records, including 12 sprinters and 12 skaters specializing in the classical all-round events. The tests found significant differences in the sample anthropometric characteristics, strength and functionality test indices. The multi-factorial group test data analysis (with both of the groups virtually identical in the sport specialization, age structure and qualifications) found significant intergroup differences in the special physical working capacity indices.